A review of 3D printed patient specific immobilisation devices in radiotherapy. (January 2020) - Asfia, Amirhossein; Novak, James I.; Mohammed, Mazher Iqbal; Rolfe, Bernard; Kron, Tomas
Highlights: Investigating 3D printed immobilization devices. Comparing the 3D printed immobilization devices with traditional ones. Investigating the technical fabrication details of the articles. Introducing the scope, testing and results of the studied literatures. Abstract: Background and purpose: Radiotherapy is one of the most effective cancer treatment techniques, however, delivering the optimal radiation dosage is challenging due to movements of the patient during treatment. Immobilisation devices are typically used to minimise motion. This paper reviews published research investigating the use of 3D printing (additive manufacturing) to produce patient-specific immobilisation devices, and compares these to traditional devices. Materials and methods: A systematic review was conducted across thirty-eight databases, with results limited to those published between January 2000 and January 2019. A total of eighteen papers suitably detailed the use of 3D printing to manufacture and test immobilisers, and were included in this review. This included ten journal papers, five posters, two conference papers and one thesis. Results: 61% of relevant studies featured human subjects, 22% focussed on animal subjects, 11% used phantoms, and one study utilised experimental test methods. Advantages of 3D printed immobilisers reported in literature included improved patient experience and comfort over traditional methods, as well as high levels of accuracy between immobiliser and patient, repeatable setup, and similar beam attenuation properties to thermoformed immobilisers. Disadvantages included the slow 3D printing process and the potential for inaccuracies in the digitisation of patient geometry. Conclusion: It was found that a lack of technical knowledge, combined with disparate studies with small patient samples, required further research in order to validate claims supporting the benefits of 3D printing to improve patient comfort or treatment accuracy.